Implementasi Low Power Mode Berbasis Finite State Machine Pada Sistem Pelacak Lokasi Parkir Mobil Menggunakan GPS Module Dan GSM Module - Agung Wismawan Rochmatullah; Dahnial Syauqy; Mochammad Hannats Hanafi Ichsan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Confusion and forget the location of the parking lot is something that usually happen. Especially for car users who park in a large area or in newly visited areas, it is troublesome for the user to find the car. Based on this problem, its needed a system that can help users to find the location of cars that have been parked via an android smartphone. In order to save the power, this system using finite state machine method that aims to apply the principle of low power work by using several states, that is sleep and wake. This system uses GPS Neo 6m which serves to get the coordinate point value of the car being parked, SIM800L serves for sending data to the user's smartphone applications, ATmega328p serves as processing input and output of the system, and the android smartphone applications to display the location to google maps. Based on the tests that have been done, the result obtained the average rating of current savings on the SIM800L components are 0.46A. It is hoped that this research can help cars users who is confused or forgotten about the location of their car park.